THE TEACHER´S TRAINING IN THE FIELD OF LEADERSHIP - STEJSKALOVÁ, Irena; SLÁMA, Jiří; PŘIBYL, Vladimír; KOMÁRKOVÁ, Lenka (Trends in education, 2021)
Changes in society place demands on the role of the teacher in teaching, who should, in addition to knowledge, also expand the portfolio of competencies and other useful tools applicable in teaching when communicating with pupils. This paper presents the experience with a recently accredited education program for teachers in the field of leadership carried out at one managerial faculty. The aim of the paper is to evaluate the benefits of this non-formal education using a two-round questionnaire survey. All 31 participants in the program took part in the survey. We found that too many participants did not encounter the concept of leadership in previous either formal or vocational education. After getting acquainted with this concept within the program, there was a significant development of communication skills. The textual answers showed that the participants learned how to influence the pupils' behaviour by changing their own behaviour. Therefore, the combination of managerial and pedagogical approaches in teaching seems to be very useful.
Keywords: training; leadership; competencies; communication